(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The COVID-19 pandemic has significantly disrupted economies around the world, and Uzbekistan is no exception. As the country embarks on a post-pandemic recovery path, the concept of inclusive growth has gained prominence as a key strategy for ensuring sustainable economic development. This article examines the challenges and opportunities that Uzbekistan faces in achieving inclusive growth in the post-COVID-19 era. Key challenges include rising inequality, vulnerable labor markets, and regional disparities. However, the pandemic has also provided opportunities to advance digitalization, reform social protection systems, and promote green growth. By analyzing recent economic data and policy initiatives, this article highlights the need for targeted government interventions, investments in human capital, and promotion of innovative industries to promote inclusive growth. The findings highlight that inclusive growth in Uzbekistan can be achieved through a combination of economic diversification, equitable resource distribution, and strengthened social policies that support the most vulnerable in society.